866 Paediatric Stool Testing Practices in Ireland and Potential Influence on Epidemiology of Rotavirus Gastroenterisis (RVGE) and Rotavirus Immunisation. (October 2012) - Carroll, F; Powell, J; McMahon, R; O'Rourke, D; O'Donnell, C; Dooly, T; O'Connell, N; Fitzgerald, R; Philip, RK
Abstract : Background and Aims: Rotavirus vaccination has not been taken up in Ireland. We aimed to conduct a regional audit of gastroenteritis and paediatric stool testing patterns to generate better epidemiological data to support a rotavirus vaccination programme in Ireland. Methods: A retrospective audit of infants and children< 5yrs with Hospital Inpatient Enquiry (HIPE) coded gastroenteritis admitted between 2005 and 2010. Stool testing patterns from the community and hospitals, from the Mid-West Ireland was analysed. Trends of Roatvirus, Adenovirus, Bacterial, Stool test Negative gastroenteritis was tabulated. Audit was approved by hospital audit committee. Results: The incidence of rotavirus in the tested paediatric population is 26% and that of adenovirus is 5%. Rotavirus peaked in 2006 with 30% testing positive, compared with 22% in 2008 and 25% in 2010. The positive pick up rate for stool culture & sensitivity (C&S) by community clinicians and Hospital respecively was 4%, 7% and 9% in 2001, 2006 and 2010. While only 1640 stool samples were tested for rotavirus over 5 years, 7534 samples were tested for C&S with the vast majority not warranting any anti-microbial treatment. In a 5 yr period, GPs in community only requested rotavirus on 287 stool samples, while testing 3353 for C&S. Conclusion: Our rotavirus epidemiological data, based on which the decision not to incorporate an oral rotavirus vaccine to the National schedule, is possibly inaccurate reflecting our stool testing practices. Further reduction of clinical burden due to RVGE could be achieved by incorporating rotavirus immunization to the National programme.